PEMANFAATAN MODEL TOTAL PHYSICAL RESPONSE DAN REPETITION UNTUK PENGEMBANGAN PEMBELAJARAN BAHASA INGGRIS ANAK USIA DINI/TK - Wijayatiningsih, Testiana Deni; Mulyadi, Dodi (Jurnal Penelitian Pendidikan, 2014)
The application of Total Physical Response and repetition model to develop young learners learning is the combination of song, movement, and language by using audio, visual, and kinesthethic. This research aims at applying young learners learning model, which consists of; to look for and select nursery rhymes and movement implemented in TPR and repetition model, to determine steps and flow is used in English young learners learning, to create learning CD, and TPR and Repetition handout, to analyze the use of TPR and repetition in young leaners learning. The significance of the research is to contribute English young learners teachers learning model so the learners are able to learn English easily and attractively. The result of this research influences positive effect towards English young learners mastery because they are able to learn and sing simultenously to memorize new vocabularies using musical movement. It can be seen from the investigation result of the use of course design and lesson plan is 71,67, the investigation result of the use of course design, lesson plan, learning CD, and TPR handout is 72,5. Moreover, the application TPR and repetition before and after learning it has improvement 34,15. From the explanation above, it can be concluded that the application of Total Physical Response and repetition model to develop young learners / kindergaten learning can be applied well and give motivation to learn English easily.